2021
DOI: 10.1111/ahe.12761
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical description of the origin and distribution of the brachial plexus to the antebrachium in one puma (Puma concolor) (Linnaeus, 1771)

Abstract: The knowledge of the anatomy of the brachial plexus in animals is of great importance due to its applicability in clinical, diagnostic and surgical procedures. The objective of the present study was to describe the anatomy of the brachial plexus in the puma. The results demonstrate a broad anatomical similarity with other felines; however, some differences were found. The formation of the brachial plexus in the puma occurred from the ventral interconnections of the last three cervical nerve segments and the fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
36
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(38 citation statements)
references
References 28 publications
2
36
0
Order By: Relevance
“…vulpes (Haligur & Ozkadif, 2021), F. catus (Hakki-Nur et al, 2020) and L. geoffroyi (Souza-Junior et al, 2018). The n. suprascapularis innervates the same muscles in all carnivoran species where supply for the muscles was reported (Barone & Simoens, 2010;Barreto-Mejía et al, 2021;Budras et al, 2007;Demiraslan et al, 2015;Dyce et al, 2012;Evans & De Lahunta, 2013;Ghoshal, 1982;Hakki-Nur et al, 2020;Pinheiro et al, 2013;Souza et al, 2010;Souza-Junior et al, 2014. Although it has been reported that also innervates the trapezius muscle in F. catus (Hakki-Nur et al, 2020), which differs from that reported in other carnivorans.…”
Section: Comparative Anatomy Of the Brachial Plexus Nerves Of P Flavu...mentioning
confidence: 70%
See 4 more Smart Citations
“…vulpes (Haligur & Ozkadif, 2021), F. catus (Hakki-Nur et al, 2020) and L. geoffroyi (Souza-Junior et al, 2018). The n. suprascapularis innervates the same muscles in all carnivoran species where supply for the muscles was reported (Barone & Simoens, 2010;Barreto-Mejía et al, 2021;Budras et al, 2007;Demiraslan et al, 2015;Dyce et al, 2012;Evans & De Lahunta, 2013;Ghoshal, 1982;Hakki-Nur et al, 2020;Pinheiro et al, 2013;Souza et al, 2010;Souza-Junior et al, 2014. Although it has been reported that also innervates the trapezius muscle in F. catus (Hakki-Nur et al, 2020), which differs from that reported in other carnivorans.…”
Section: Comparative Anatomy Of the Brachial Plexus Nerves Of P Flavu...mentioning
confidence: 70%
“…In the other species of caniformes, there are no contributions from C5 or T2, and the only contribution comes from C6-T1, such as in three members of the family Canidae as C. thous (Pinheiro et al, 2014;Souza-Junior et al, 2014), A. microtis (Pinheiro et al, 2013) and L. gymnocercus (Souza-Junior et al, 2017); one member of the family Otariidae as A. australis (Souza et al, 2010); and two members of the family Mustelidae as M. foina (Demiraslan et al, 2015) and N. vison (Backus et al, 2016). In most members of the suborder Feliformia and family Felidae, there are no contributions from C5 or T2, such as in F. catus (Aubert et al, 2004;Barone & Simoens, 2010;Ghoshal, 1982;Hakki-Nur et al, 2020;König, 1992), L. pardalis (Chagas et al, 2014), P. onca and P. concolor (Barreto-Mejía et al, 2021;. Whereas in L. geoffroyi the contribution comes mainly from C5-T1 (83.3%) (Souza-Junior et al, 2018).…”
Section: Distribution Of the Radial Nerve Towards Manus In A Male Spe...mentioning
confidence: 99%
See 3 more Smart Citations